Psychological factors and performance in women`s football: A systematic review - Dahl Pettersen, S.; Adolfsen, F.; Martinussen, M. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The amount of research conducted on female football players, compared to male players, is sparce. Even though research on female football players has increased the past decade, there is still a lack of studies of how psychological factors affect their performance. The objective of the current systematic review was therefore to summarize existing quantitative research into the relationship between psychological factors and performance in women's football. Literature was sourced from MEDLINE/PubMed, Embase, and PsychInfo. Two independent reviewers applied the selection criteria and assessed the quality of the studies. A total of 14 studies met the inclusion criteria. The total number of participants was 1449, and 15 psychological factors were examined in relation to football performance. The results revealed a tendency for higher leveled players to score higher on psychological factors like mental toughness, conscientiousness, and executive functions. They also had lower levels of anxiety. Enjoyment and a perceived mastery climate were related to increased levels of performance and perceived competence. Mood was unrelated to performance. Limitations and implications for future research are discussed.